2009
DOI: 10.1007/s12098-009-0248-1
|View full text |Cite
|
Sign up to set email alerts
|

Central hypothyroidism

Abstract: A 15-mth-old male child of consanguineous parents, presented with classical features of congenital hypothyroidism. Serum total thyroxine (T4), total triiodothyronine (T3) and TSH were low. There was no evidence of deficiency of other pituitary hormones. Magnetic resonance imaging of the pituitary was normal. TSHB gene sequencing revealed a homozygous missense mutation due to single base substitution G?A at codon 85 resulting in change from Glycine to Arginine. This mutation in TSHB gene has been reported earli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Primary hypothyroidism was associated with decreased odds of spontaneous labour and increased odds of Caesarean section Study done by Krishnan M et al observed more cases of Caesarean sections in hypothyroidism (62.2%) and present figure is (60.8%) being in the par with that of the above. 20 In present study more of EM.LSCS were observed both in hypo and hyperthyroid cases. Still birth (SB) rate among overt hypothyroids was 2.9% in the study of Sahu M et al and study of Robert Negro et al showed the SB rate of 3.9% vs 0% in overt hypo and hyper thyroids respectively.…”
Section: Resultssupporting
confidence: 57%
“…Primary hypothyroidism was associated with decreased odds of spontaneous labour and increased odds of Caesarean section Study done by Krishnan M et al observed more cases of Caesarean sections in hypothyroidism (62.2%) and present figure is (60.8%) being in the par with that of the above. 20 In present study more of EM.LSCS were observed both in hypo and hyperthyroid cases. Still birth (SB) rate among overt hypothyroids was 2.9% in the study of Sahu M et al and study of Robert Negro et al showed the SB rate of 3.9% vs 0% in overt hypo and hyper thyroids respectively.…”
Section: Resultssupporting
confidence: 57%
“…The results of this case series of patients with the X-linked IGSF1 deficiency syndrome, the largest to date, reveal new symptoms and expand the information on previously reported symptoms. Despite having been discovered only recently, this syndrome already encompasses more unique mutations and patients than all other known genetic causes of isolated central hypothyroidism combined ( TSHB [ 12 16 ] and TRHR [ 17 , 18 ]). An overview of the clinical features of IGSF1 deficiency is presented in Table 3 , and recommendations for genetic evaluation and clinical management are provided in Table 4 .…”
Section: Discussionmentioning
confidence: 99%